2002
DOI: 10.1067/mnc.2002.125915
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia in Kawasaki disease: Evaluation with dipyridamole stress technetium 99m tetrofosmin scintigraphy

Abstract: Tetrofosmin myocardial perfusion imaging can detect regional hypoperfusion in children with KD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…It is well known that CAG and SPECT are consistent with coronary artery stenosis. 9,13,18 SPECT is a highly sensitive, but non-specific technique in detecting coronary artery stenosis, as patients show perfusion defects according to the degree of obstruction and lack of collateral circulation. This concordance is better in adults because of the higher homogeneity of coronary lesions due almost exclusively to arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that CAG and SPECT are consistent with coronary artery stenosis. 9,13,18 SPECT is a highly sensitive, but non-specific technique in detecting coronary artery stenosis, as patients show perfusion defects according to the degree of obstruction and lack of collateral circulation. This concordance is better in adults because of the higher homogeneity of coronary lesions due almost exclusively to arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fukuda et al observed among children with Kawasaki's disease that coronary artery stenoses may be visualized with dipyridamole stress technetium 99m tetrafosmin SPECT with a sensitivity of 90% and specificity of 100%. 6 However, Fu et al observed that coronary aneurysms without stenoses are more difficult to detect, with only 30% exhibiting abnormal perfusion images. 7 CCTA easily visualizes extraluminal remodeling and may provide a noninvasive alternative to angiography for evaluation of coronary artery aneurysms.…”
Section: Discussionmentioning
confidence: 98%
“…Сцинтиграфия дает возможность обнаружить как ранние признаки ишемии, так и тяжелые рубцо-вые поражения. Чувствительность метода возрастает при применении физической или фармакологической нагрузки [44,45]. Высокая лучевая нагрузка ограничи-вает его применение.…”
Section: непрерывное профессиональное образованиеunclassified